TELAAH META-SINTESIS ATAS KONSEP PENDIDIKAN SEPANJANG HAYAT DALAM AL-QUR'AN: KONVERGENSI ANTARA TAFSIR MAUDHU'I DAN FILSAFAT PENDIDIKAN KONTEMPORER - Redho Qurrota A’yun, Ahmad; Saeful Ahyar, Ahmad; Amirudin; Gani, A.; Akmansyah, M. (As-Sulthan Journal of Education, 2026)
This study aims to construct a philosophical framework of lifelong learning through a meta-synthesis of key concepts in the Qur'an using the thematic interpretation (tafsir maudhu'i) approach, while identifying points of convergence and divergence with contemporary educational philosophy discourse. Employing a philosophical meta-synthesis method with systematic literature review, this research collects and analyzes Qur'anic verses on knowledge, intellect, and learning, and compares them with paradigms of progressivism, humanism, and critical education. The findings indicate that the Qur'an constructs a holistic, integrative, and transcendentally teleological concept of lifelong education (based on ‘ubūdiyyah and khalīfah). Significant convergence is found in the emphasis on active, contextual, learner-centered, and decentralized learning. However, the Qur'an offers a theocentric foundation that provides deep meaning and intrinsic motivation, while also serving as a correction to the tendencies of extreme instrumentalism and secularism in some contemporary streams. The resulting synthesis offers a paradigm of lifelong education that is liberating, meaningful, and relevant for developing educational policies and practices in contemporary Muslim societies.